1994
DOI: 10.1071/pp9940393
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Wheat Phasic Development to Major Environmental Factors: a Re-Examination of Some Assumptions Made by Physiologists and Modellers

Abstract: In this review we assess the universality of several assumptions that are commonly made about development in wheat. The assumptions tested are that: (1) wheat is most sensitive to the environmental variables of temperature and photoperiod during the vegetative period; (2) any responses to vernalisation and photoperiod are complete by the time that the apex has become reproductive and the stems begin to elongate; (3) cultivars differ little in their responses to temperature aside from any r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
255
1
34

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(313 citation statements)
references
References 75 publications
23
255
1
34
Order By: Relevance
“…2d). Phase 3 is simplest to analyze because temperature appears to be the only major factor affecting its duration (Slafer and Rawson, 1994). Our results showed that phase 3 was three days shorter in Iwainodaichi than in Chikugoizumi when seeded early (Table 2).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…2d). Phase 3 is simplest to analyze because temperature appears to be the only major factor affecting its duration (Slafer and Rawson, 1994). Our results showed that phase 3 was three days shorter in Iwainodaichi than in Chikugoizumi when seeded early (Table 2).…”
Section: Resultsmentioning
confidence: 69%
“…In this paper, the developmental stage from sowing to double ridge is called phase 1, that from double ridge to anthesis phase 2 and that from anthesis to maturity phase 3. Each phase responds to environmental factors differently (Slafer and Rawson, 1994). Among the environmental factors, temperature is considered to be the most important and universal one.…”
mentioning
confidence: 99%
“…During the 20 th century, wheat (and to a similar extent barley) production increased in some European regions by more than 6-fold (e.g. Slafer & Rawson 1994). This increase was initially due to an expansion in harvested area that occurred during the first half of the century, which was followed from the 1950s onwards by an increase of ca.…”
Section: Introductionmentioning
confidence: 92%
“…wheat (Slafer & Rawson, 1994) and barley (Willey & Holliday, 1971). Moreover, the experimental decrease of competition for assimilates by removing tillers from the plant in spring wheat resulted in lower floret abortion (Mohamed & Marshall, 1979).…”
Section: Interrelationships Between the Characters Studiedmentioning
confidence: 99%